MANAJEMEN PERUBAHAN, DAN FAKTOR-FAKTOR PENYEBAB DALAM PERUBAHAN ORGANISASI - Rosnaeni, Yeni; Hayadi, Herawan; Ali Yusuf, Furtasan (MANTRA (Jurnal Manajemen Strategis), 2024)
Change management is a systematic process of applying the knowledge, tools and resources needed to influence change in the people who will be affected by the process. Change management is also understood as an effort taken by managers to manage change effectively, which requires an understanding of the issues of motivation, leadership, groups, conflict, communication and discipline. Thus, change management must have a good strategy, in accordance with the current situation and conditions. or will happen. In change management, strategies for dealing with reluctance to change are very important. Failure to overcome reluctance to change cannot be separated from human error, organizational actors, in responding to system changes, from the previous system to the new modern organizational system. This tries to convey things that can be done to anticipate resistance that arises due to the unpreparedness of organizational actors towards system change. This is important because unpreparedness to accept system changes is often the cause of organizational implementation being rejected. Didn't feel like they had a new system because they weren't involved in the planning; the assumption that applying resistance to change in the organization will disrupt habits; and other negative thoughts can become obstacles to implementing e-government. By knowing the causes or reasons for resistance to changes in organizational systems, better change management efforts can be made, so that in the face of reluctance to change it can be successful as expected.